The Functionality of Probiotic Bacteria Microencapsulation by Spray Drying: A Literature Review - Hanidah, In-In; Kirana, Annisa Indah; Nurhadi, Bambang; Sumanti, Debby Moody (Department of Agro-industrial Technology, University of Brawijaya, 2021)
AbstractProbiotic-based products are associated with many health benefits. The viability of probiotics is necessary to provide health benefits, but it is lost during processing, storage, and gastrointestinal tract. The viability of probiotics can be maintained by applying the spray drying encapsulation technique. This review article discusses probiotic bacteria, encapsulant ingredients, the principle of spray drying in microencapsulation, and the functional properties of spray drying probiotic microcapsules. This article uses a non-research method with a literature review of various sources such as research journals and related books. Based on existing studies, the viability of probiotic spray drying results is influenced by the bacterial culture used, the type and concentration of the encapsulated material, and the spray drying conditions (feed temperature, inlet temperature, and outlet temperature). Probiotic microcapsules spray drying has excellent potential in functional food formulations, and its commercial applications will benefit both the industry and consumers.Keywords: functionality, microencapsulation, probiotics, spray drying, viability AbstrakProduk berbasis probiotik sering dikaitkan dengan banyak manfaat kesehatan. Viabilitas probiotik diperlukan untuk memberi manfaat kesehatan, tetapi hal tersebut hilang selama pemrosesan, penyimpanan, dan melewati saluran pencernaan. Viabilitas probiotik dapat dipertahankan dengan penerapan teknik enkapsulasi pengeringan semprot. Review artikel ini membahas mengenai bakteri probiotik, bahan enkapsulasi, prinsip pengeringan semprot dalam mikroenkapsulasi, dan sifat fungsional mikrokapsul probiotik pengeringan semprot. Penulisan artikel ini menggunakan metode non-research dengan literature review berbagai sumber, seperti jurnal penelitian dan buku yang terkait. Hasil review artikel memberikan informasi bahwa viabilitas probiotik hasil pengeringan semprot dipengaruhi oleh spesies dan strain bakteri yang digunakan, jenis dan konsentrasi bahan enkapsulasi, serta kondisi pengeringan semprot (suhu umpan, suhu masuk, dan suhu keluar). Mikrokapsul probiotik pengeringan semprot memiliki potensi besar dalam formulasi pangan fungsional sehingga aplikasi komersialnya akan menguntungkan industri dan konsumen.Kata kunci: fungsionalitas, mikroenkapsulasi, pengeringan semprot, probiotik, viabilitas